Jugong as Traditional Fishermen's Formal Aesthetics in Karangtalun Village, Cilacap - Rochyat, Indra Gunara; Noor, Firdaus; Yusuf, Adisti Ananda; Wiyono, Erina (Mudra Jurnal Seni Budaya, 2024)
Jugong is a traditional fishing boat that holds great significance for the fishing community in Karangtalun Village, Cilacap. It is valued for its aesthetic qualities that are expressed through its unique characteristics. This paper explores the functional value of the jugong, the process of its creation by the fishermen, and the artistic expression involved in its design, with the ultimate goal of revealing the aesthetic value of the jugong in general. In order to approach, understand, and reveal the aesthetic values of the jugong, which comes from the village fishermen as cultural actors, this research uses the ethnoart perspective as a method. In order to reveal the functional values, we use functional aesthetic theory as an approach method. In addition, to understand how fishermen create jugong, we use mimetic style theory and the aesthetic theory of expression to reveal the fishermen's attitude and behavior during the process of jugong creation. The study results show that the aesthetic value of the jugong is reflected in the traditions that impose strict rules on the fishermen. The community also appreciates the sensitive attitude of the fishermen towards their cultural products by respecting their identity and pride, which includes their aesthetics.